Studi Perhitungan Dan Penyetelan Rele Jarak Sebagai Pengaman Utama Saluran Udara Tegangan Tinggi 150 KV - Arifin, Ayub Qoirul; , Umar, ST.MT (2016)
Disruption that often occurs in the power system is on the transmission line. Disorders that may be a two-phase, three-phase, single phase to earth, lightning strikes, or break up channel. Therefore, the use of a safety relay is absolutely necessary to protect and prevent the spread due to interference and can accelerate recovery system from interference. Their new conductor in Priok Baru - Plumpang 150kV High Voltage (HV) it needed the adjustment relay, with the intention that the function relays work according to its function. HV new 150 kV Priok - Plumpang use within the type Micom P443 relay as the primary safety channel. It is known that the characteristics of Quadramho used as a safety relay SUTT distance of 150 kV Priok Baru - Plumpang. Based on the above problems, the coordination of the setting of distance relays installed in Gas Insulated Substation (GIS) Priok Baru and substation should be determined Plumpang value. In order along the channel can be guaranteed level of security against in terference between phase and phase to earth disturbance then obtained setting value zone 1 of 2.02 Ω ∠76 °, zone 2 amounted to 3,02 ∠ 76° Ω and zone 3 of 11.6 ∠ 760Ω.